Sustainability Through Higher Education - Herrera Gutierrez, Daniela Carolina; Arias Devia, Karen Lorena; Ramos Gomez, Edna Vanessa (Journal of Sustainability Perspectives, 2021)
The Universidad Nacional Abierta y a Distancia, UNAD, through instruments, the experiences in environmental management and their participation in the UI GreenMetric World University Rankings were systematized. This article shows the implementation of sustainability within the institution, which was achieved through the Participatory Action methodology, which facilitates the integration of knowledge and actions to promote transformations in the thinking of the institutional community. In this way, they are articulated: objectives, strategy (ecological homes), research, technology and ICT as a method to establish relationships between the university, the State and the community. Additionally, the university defines projects and goals in the 2019-2023 development plan, which are articulated to comply with the Sustainable Development Goals, to train the community in values such as solidarity, assertive and true communication, collaboration effective, the attitudes to dialogue comprehensively, for the benefit of current and future generations. Therefore, only through interdisciplinary work, it is and will be possible to solve the problems that the world must face, seeking to curb hyperconsumption and social irresponsibility, which by seeking economic benefits for certain sectors puts the lives and survival of the species that inhabit the planet, including the human race itself at risk. According to this, the UNAD has the commitment from the environmental management to articulate efforts for the elaboration of proposals that allow the implementation of responsible consumption routes and collective action for the care of the environment